Peningkatan Kompetensi Pengembangan Aplikasi Akuntansi Berbasis Microsoft Excel pada Siswa SMK Triguna 1956 - Desy Mariani; Desi Anggraeni; Suryani Suryani; Puspita Rani (Jurnal Relawan dan Pengabdian Masyarakat REDI, 2024)
The need for fast and accurate financial information is increasing along with the increasingly complex and fast business processes in the world. Therefore, workers, especially in the accounting sector who are tasked with providing financial information, are required to be able to utilize technology to support the company's financial recording and reporting process. Triguna 1965 Vocational School as a secondary education institution which aims to prepare its students as professionals needs to get support to be able to fulfill this goal. The aim of this community service activity is to help improve the competency of Triguna 1956 Vocational School students in developing automated accounting applications based on Microsoft Excel. By increasing students' competency in using Microsoft Excel, especially in developing accounting applications or other financial applications, this will really train their logical thinking and the level of efficiency and effectiveness in their work later.